[18F]F-FMISO and [18F]F-FLT PET/CT dual-nuclide imaging for in vivo prediction of drug resistance in pancreatic cancer - SUN Chenwei; HAI Wangxi; QU Qian; XI Yun (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·[18F]F-FMISO and [18F]F-FLT are specific PET imaging agents for detecting the hypoxia microenvironment and cell proliferation, respectively. This study aims to visualize and monitor the impact of drug resistance in pancreatic cancer on the hypoxia microenvironment and cell proliferation through [18F]F-FMISO and [18F]F-FLT PET/CT dual-nuclide imaging, with the goal of providing a theoretical basis for clinical application.Methods·The CCK-8 assay was conducted to assess drug resistance in the PANC-1/R (PR) pancreatic cancer cell line compared to the parental PANC-1 (P) cell line. Subcutaneous xenograft models of pancreatic cancer were established by injecting male BALB/c nude mice with pancreatic cancer cells into the left axillary subcutaneous region. Subgroups were treated with gemcitabine (GEM) chemotherapy starting on day 18 (18D-G group) or day 12 (12D-G group) after inoculation of tumor cells. [18F] F-FMISO and [18F] F-FLT PET/CT imaging were performed before and after treatment to obtain semi-quantitative parameters (maximum standardized uptake value, SUVmax). ΔSUVmax was calculated by using the following equation: ΔSUVmax=(SUVmax of second imaging-SUVmax of first imaging)/ SUVmax of first imaging. Receiver operating characteristic (ROC) curves were used to determine the optimal threshold for the semi-quantitative parameters to assess pancreatic cancer drug resistance.Results·The CCK-8 assay confirmed that the PR cells exhibited high resistance to GEM, with a resistance index of 4.24 (n=5). In vivo experiments showed that GEM chemotherapy significantly inhibited tumor growth and prolonged survival in the parental pancreatic cancer group (12D-G group, P=0.025), whereas GEM chemotherapy accelerated tumor growth and shortened survival (18D-G and 12D-G, P=0.025) in the drug-resistant pancreatic cancer group. In addition, in the non-chemotherapy group, ΔSUVmax-FLT might be negatively correlated with survival time, while in the chemotherapy group, both ΔSUVmax-FMISO and ΔSUVmax-FLT were negatively correlated with survival time (P=0.050, P=0.006). In the 18D-G and chemotherapy group, the second imaging showed significantly lower ΔSUVmax-FMISO and ΔSUVmax-FLT in P tumors compared to PR tumors (P=0.045, P=0.050). In the 12D-G and chemotherapy group, the second imaging showed slightly lower ΔSUVmax-FLT in P tumors compared to PR tumors (P=0.051). ROC analysis identified the optimal threshold for assessing pancreatic cancer drug resistance: when ΔSUVmax-FLT=0.45 in the non-chemotherapy group, the sensitivity and specificity were 100.00% and 50.00%, respectively; when ΔSUVmax-FMISO=0.37 and ΔSUVmax-FLT=0.36 in the chemotherapy group, the sensitivity and specificity were 100.00% and 83.33%, respectively.Conclusion·[18F]F-FMISO and [18F]F-FLT PET/CT dual-nuclide imaging can be used to assess drug resistance in pancreatic cancer. The comparison of [18F]F-FMISO and [18F]F-FLT PET differences before and after chemotherapy provides the most accurate prediction of drug resistance and survival time.